MODEL SELEKSI PADA ASURANSI JIWA DWIGUNA DENGAN UANG PERTANGGUNGAN MENINGKAT - Julianty, Dila Tirta; Kho, Johannes; ', Aziskhan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses the use of select model on endowment increasing insurance in determining premium for person currently aged x+s , who was selected at age with ℎyear selection period. Premiums covered are premiums payable times a year, based on calculation of gross premium by considering the management expenses of insurance company. The calculation of the premiums payable times a year is influenced by the life annuities-due and determinedusing the approximation under the uniform distribution of death assumption and expressed in commutation function.